Cross-coupling of vinylethylene carbonates with arylboronic acids catalyzed by in situ generated palladium nanoparticles in water. Issue 30 (27th July 2016) - Mao, Yuxue; Zhai, Xing; Khan, Ajmal; Cheng, Jiong; Wu, Xue; Zhang, Yong Jian
Graphical abstract: Highlights: The coupling of vinylethylene carbonates with arylboronic acids has been developed. The coupling reaction was catalyzed by in situ generated palladium nanoparticles. The process gave 4-hydroxylprenylarenes and their derivatives in high yields. Abstract: A practical and greener method of the cross-coupling of vinylethylene carbonates (VECs) with arylboronic acids has been described. The coupling reaction was catalyzed by in situ generated palladium nanoparticles (PdNPs) without any ligands and additional stabilizers in water under ambient conditions to provide useful 4-hydroxylprenylarenes and their derivatives in good to high yields.